Perbedaan individu di dalam psikologi pendidikan - Mardiani Bebasari; Neviyarni Suhaili (Indonesian Journal of Counseling and Development, 2022)
Individual differences in education explain differences related to students' differences in thinking, feeling, and acting in the same class. The purpose of writing this article is to explain how individual differences in learning and education understand the uniqueness of each individual. This research method uses literature study to examine through writings from books about individual differences. Research result There are three aspects of individual differences that must be considered by teachers and principals in a teaching and learning process, which include biological differences, intellectual differences, and psychological differences. On individual differences, the efforts that must be made by teachers in the classroom include using (1) improvement programs, (2) enrichment programs, (3) acceleration programs, (4) individual learning programs, (5) programs that specialize children for independent learning. Every educator needs to have knowledge of educational psychology. The conclusion is Educational psychology is a branch of psychology that specializes in understanding teaching and learning in an academic environment. Educational psychology has an extensive scope. The central problem in educational psychology is the problem of learning. On individual differences found differences between one individual and another in terms of personality and intelligence